Determinants of Financial Distress During COVID-19 - Adessa Wibin; Yanti Yanti (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to analyze the effect of liquidity, leverage, profitability, sales growth, and operating capacity on financial distress during the COVID-19 period. Quantitative research is used using secondary data with purposive sampling method involving 55 hotel, restaurant, tourism, and transportation companies taken from financial statement on IDX. The research methods used are multiple linear regression analysis and analyzed utilizing IBM SPSS. This study during COVID-19 carries out that leverage has an effect on financial distress, while liquidity, profitability, sales growth and operating capacity have an insignificant effect on financial distress.